Use of varenicline for smoking cessation treatment in UK primary care: an association rule mining analysis - Huang, Yue; Lewis, Sarah; Britton, John (BioMed Central, 2014)
BACKGROUND: Varenicline is probably the most effective smoking cessation pharmacotherapy, but is less widely used than nicotine replacement therapy. We therefore set out to identify the characteristics of numerically important groups of patients who typically do, or do not, receive varenicline in the UK.